NEW METHOD OF CULTIVATING PEACH ORCHARDS (Spectrum Journal of Innovation, Reforms and Development, 2023)
The results of studies where the introduction of optimized met hods of tree formation are established allow the creation of intensive peach orchards from strong-growing trees, where the density of standing is 1000 bushes (5x2 m.).